Use of Intravenous Iron Supplementation in Chronic Kidney Disease: an Update (Iranian Journal of Kidney Diseases, 2013)
Iron deficiency is an important clinical concern in chronic kidney disease (CKD), giving rise to iron-deficiency anemia and impaired cellular function. Oral supplementation, in particular with ferrous salts, is associated with a high rate of gastrointestinal side effects and is poorly absorbed, a problem that is avoided with intravenous iron. The most stable intravenous iron complexes (eg, iron dextran, ferric carboxymaltose, ferumoxytol, and iron isomaltoside 1000) can be given in higher single doses and more rapidly than less stable preparations (eg, sodium ferric gluconate). Iron complexes that contain dextran or dextran-derived ligands can cause dextran-induced anaphylactic reactions, which cannot occur with dextran-free preparations such as ferric carboxymaltose and iron sucrose. Test doses are advisable for conventional dextran-containing compounds. Iron supplementation is recommended for all CKD patients with anemia who receive erythropoiesis-stimulating agents, whether or not they require dialysis. Intravenous iron is the preferred route of administration in hemodialysis patients, with randomized trials showing a significantly greater increase in hemoglobin levels for intravenous versus oral iron and a low rate of treatment-related adverse events. In the nondialysis CKD population, the erythropoietic response is also significantly higher using intravenous versus oral iron, and tolerability is at least as good. Moreover, in some nondialysis patients intravenous iron supplementation can avoid, or at least delay, the need for erythropoiesis-stimulating agents. In conclusion, we now have the ability to achieve iron replenishment rapidly and conveniently in dialysis-dependent and nondialysis-dependent CKD patients without compromising safety.